Long-term efficacy and safety of RazumabTM (biosimilar ranibizumab) in Indian patients with retinal diseases: results from retrospective REAR RD-2 study - Sharma, Shashikant; Chaturvedi, Alok; Dave, Nilanj; Shah, Ankita (International Journal of Clinical Trials, 2022)
Background: To evaluate risk factors associated with retinal diseases and efficacy and safety of RazumabTM (biosimilar ranibizumab) in the management of retinal diseases in Indian patients with wet age-related macular degeneration (wet AMD), diabetic macular edema (DME), retinal vein occlusion (RVO) and myopic choroidal neovascularization (mCNV). Methods: In the retrospective, observational REAR RD-2 study, all patients with retinal diseases who were treated with biosimilar ranibizumab were included from multiple Indian sites. The demographic parameters, disease characteristics and treatment details were recorded. Efficacy assessments included improvement in best corrected visual acuity (BCVA), and decrease in central subfield thickness (CSFT), intra-retinal fluid (IRF) and sub-retinal fluid (SRF) from baseline to week 48. Results: Data of 1422 patients (wet AMD-27.57%; DME-30.7%, RVO-33.47%; mCNV-5.48%), who were treated with biosimilar ranibizumab, was analyzed. The most common age group of patients was 61-70 years (36.6%). The most common ocular risk factor identified was glaucoma (24.90%). A total of 85.72% patients were treatment naïve and 14.28% were previously treated patients. Biosimilar ranibizumab treatment resulted in significant (p<0.05) improvements in the mean BCVA and CSFT, and the proportion of patients with IRF and SRF was significantly reduced throughout the treatment. No new safety concerns with biosimilar ranibizumab were observed. Conclusions: Retinal diseases are more common in the age group of 61-70 years. Glaucoma was the most common ocular risk factor identified for retinal diseases. Long-term treatment with biosimilar ranibizumab was effective and well-tolerated in retinal diseases including wAMD, DME, RVO and mCNV in real-world Indian scenario.